2021
DOI: 10.1371/journal.pone.0243362
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of catastrophic wind on southern US coastal forests: Lessons from a major hurricane

Abstract: Threats posed by windstorms are an increasing concern to forest managers in the southern United States (US). Studies suggest that the southern US will experience an increase in the occurrence as well as the intensity of windstorms, such as hurricanes, in the future. However, forest managers may have difficulty preparing for this future because there is limited understanding of how windstorms affect the structure and composition of forests over the long term. In this study, we evaluated the impacts of Hurricane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…In the affected plots, the average aboveground carbon loss was estimated to be about 26 metric ton/ha. Our results were consistent with previous research that found hurricanes caused the most damage to large-diameter stands in major forest types in the southeastern US (Ojha et al, 2020;Platt et al, 2000;Sharma et al, 2021;Zampieri et al, 2020). (Chevalier et al, 2022a, b) applied experimental forest management techniques by trimming the canopy to regenerate aboveground carbon but reported continued carbon loss in larger trees after severe Hurricane Maria.…”
Section: Discussionsupporting
confidence: 92%
“…In the affected plots, the average aboveground carbon loss was estimated to be about 26 metric ton/ha. Our results were consistent with previous research that found hurricanes caused the most damage to large-diameter stands in major forest types in the southeastern US (Ojha et al, 2020;Platt et al, 2000;Sharma et al, 2021;Zampieri et al, 2020). (Chevalier et al, 2022a, b) applied experimental forest management techniques by trimming the canopy to regenerate aboveground carbon but reported continued carbon loss in larger trees after severe Hurricane Maria.…”
Section: Discussionsupporting
confidence: 92%
“…This sensitivity to land management may be especially relevant in forested land, which is the predominant land cover type in catchments of the Florida Panhandle and southern Alabama (Le et al, 2015), and especially in the lower portions of the Escambia and Choctawhatchee River catchments. In addition to timber harvesting potentially leading to increased low-flow conditions, high-intensity hurricanes that altered forest cover in the 21st Century (Sharma et al, 2021) Waterbody identification within Perdido Bay system with at least 10 years of data, illustrating significant increasing, decreasing, or no trend observed (α = 0.05) with long-term datasets indicated by darker symbols and short-term in lighter symbols for turbidity (red/pink), total suspended solids (orange/ yellow), and salinity (dark gray/white).…”
Section: Variations In Low Flow Trendsmentioning
confidence: 99%
“…The main purpose behind the extra step of preparedness is the assurance of less mortality rate and the fastest recovery despite the extreme disasters. The scenario above can be best understood by the examples of Florida (US), which recovered from multiple hurricanes [7], recovery of Japan from the 1995 earthquake [8], and Darwin, Australia recovered when prone to Cyclone Tracy with 70% destruction of building [9].…”
Section: B Natural and Technological Hazardsmentioning
confidence: 99%